Model kultury politycznej Marka Sobolewskiego - Małgorzata Kułakowska; Piotr Borowiec (Politeja)
MAREK SOBOLEWSKI’S MODEL OF POLITICAL CULTURE AS AN EXAMPLE OF ADAPTATION OF GABRIEL ALMOND’S THEORETICAL CONCEPT TO THE CONDITIONS OF THE SOCIALIST SOCIETY